Hyoid osteoradionecrosis associated with carotid rupture: Report of 2 cases1. Issue 2 (19th December 2012) - Chard, Rachel; Monroe, Marcus M.; Andersen, Peter E.
Abstract Background Osteoradionecrosis (ORN) of the hyoid bone is a rare but reported complication of head and neck irradiation. Here we describe 2 cases in which carotid rupture was associated with hyoid ORN. Methods This study was conducted through a retrospective chart review and case reports of 2 patients. Results Both patients had a history of radiation therapy for head and neck cancer; 1 patient had undergone previous surgical resection. Both patients had a history of painful swelling in the neck preceding presentation with hemorrhage. Acute hemorrhage was controlled in all patients using a combination of techniques including embolization, stent grafting, and vessel ligation. Conclusion ORN of the hyoid can be associated with life‐threatening carotid rupture. In patients with a history of head and neck irradiation who present with painful swelling in the region of the hyoid, this entity should be considered. Early intervention may prevent subsequent rupture of the carotid artery and hemorrhage. © 2011 Wiley Periodicals, Inc. Head Neck, 2013